Boston, July 21, 1789. Sir, It being now considered as an established truth ... that marks of apparent death may subsist without any necessary implication of an absolute extinction of the animating principle ; a number of gentlemen in the town of Boston ... set on foot a society, whose principal object was to disseminate the knowledge of the means proper to be used for the restoration of persons apparently dead from drowning or other causes . ([Printed by Adams and Nourse?], 1789)
Application, in the form of a circular letter, "made to some principal gentlemen ... requesting their influence ... to encourage and promote" the Humane Society of the Commonwealth of Massachusetts.